2012
DOI: 10.5056/jnm.2012.18.4.399
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the Effects of Vardenafil on Esophageal Function Using Multichannel Intraluminal Impedance and Manometry

Abstract: Background/AimsTo evaluate the effects of the phosphodiesterase type 5 (PDE5) inhibitor vardenafil on esophageal function, including bolus transit, using multichannel intraluminal impedance and esophageal manometry (MII-EM).MethodsSixteen healthy volunteers (15 men) underwent an MII-EM study including 10 liquid swallows and 10 viscous swallows in a seated position after fasting. Then, each subject was asked to ingest 50 mL distilled water or 10 mg vardenafil dissolved in 50 mL water, in a double-blind manner. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…In the 14 included studies, two trials comprised healthy control subjects alongside patients with esophageal motility disorders [ 13 , 14 ], five studies conducted as a before/after trial on patients with esophageal motility disorders [ 16 , 18 , 20 , 22 , 25 ], and four trials conducted as RCT on healthy subjects [ 5 , 6 , 12 , 21 ]. Sildenafil was used in 11 studies [ 5 , 6 , 12 16 , 19 , 20 , 22 , 24 ]; one study only used vardenafil [ 21 ], and two studies only used tadalafil [ 18 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In the 14 included studies, two trials comprised healthy control subjects alongside patients with esophageal motility disorders [ 13 , 14 ], five studies conducted as a before/after trial on patients with esophageal motility disorders [ 16 , 18 , 20 , 22 , 25 ], and four trials conducted as RCT on healthy subjects [ 5 , 6 , 12 , 21 ]. Sildenafil was used in 11 studies [ 5 , 6 , 12 16 , 19 , 20 , 22 , 24 ]; one study only used vardenafil [ 21 ], and two studies only used tadalafil [ 18 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Nine studies have reported the LES pressure after using PDE-5 inhibitors in their manometry results [ 5 , 12 14 , 16 , 19 21 , 24 ]. The use of PDE-5 inhibitors was associated with a statistically significant reduction in the LES pressure (SMD − 1.69, 95% CI: -2.39 to -0.99) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations